Integrating smart materials in powder melt extrusion 3D printing: Cassava short fiber and polyvinyl alcohol for drug delivery approach - Baramee Chanabodeechalermrung; Tanpong Chaiwarit; Pattaraporn Panraksa; Pornchai Rachtanapun; Suruk Udomsom; Pensak Jantrawut (Journal of Materials Research and Technology)
Powder melt extrusion (PME) was developed as a technique to construct polyvinyl alcohol (PVA) objects mixed with cassava short fibers (CSF), designed using CAD software, for applications in drug delivery. PVA, recognized as a smart material, exhibits the ability to change shape in response to stimuli such as heat, pH variations, or water. The physical characteristics of the 3D-printed objects including imaging, dimensions, mechanical properties, and shape-changing behavior were assessed prior to the incorporation of indomethacin. Subsequently, objects incorporating indomethacin were evaluated for their physical characteristics, thermal properties (DSC), crystalline structure (XRD), molecular interactions (FTIR), drug loading capacity, and drug dissolution behavior. Among five samples, only P, PC5.0, and PC7.5 were selected for indomethacin incorporation due to their superior physical properties. Notably, the addition of CSF and indomethacin reduced object thickness, which in turn diminished their mechanical properties. FTIR analysis confirmed the absence of chemical interactions between the materials. Furthermore, PME facilitated the conversion of crystalline PVA, CSF, and indomethacin into an amorphous form, as confirmed by XRD and DSC results. The indomethacin-loaded objects (P–I, PC5.0-I, and PC7.5-I) contained approximately 25 mg of the drug per object, and their dissolution profiles demonstrated 100% drug release within 2 h, attributable to the amorphous state of indomethacin. In conclusion, PME proves to be an effective method for constructing smart material-based objects capable of shape transformation, offering potential for innovative drug delivery approach.